The Prevalence of Gestational Diabetes and Factors Affecting it in a Health Care Center - Fatemeh Nazari Robati; Narges Khanjani; Nasrin Tabasi Nejad; Esmat Rezabeigi davarani; Mohabbat Mohseni (Kerman University of Medical Sciences, 2017)
Background & Objectives: Since late diagnosis of diabetes or missing it during pregnancy can leave severe maternal and fetal complications, and on the other hand information on the prevalence and risk factors of diabetes in pregnancy in Iran is limited, this study aimed to determine the prevalence and risk factors of gestational diabetes in Shahdad/ Kerman/ Iran. Methods: This cross-sectional, descriptive-analytical study was performed on 160 post partum women who had prenatal care files in health care center of Shahdad city from 2014 to2015. Subjects were selected through census sampling and their information was extracted from their files. Data were analyzed through SPSS version 16 and using t-test, chi-square, Fisher's exact test and logistic regression. Results: The prevalence of gestational diabetes mellitus (GDM) in the studied women was 12.5 percent. Gestational diabetes showed significant relationships with history of stillbirth (P=0.04), family history of diabetes (P<0.0001) and body mass index (0.003). In studying pregnancy outcomes, no relationship was found between the type of delivery and GDM (P=0.6), but the weight was significantly higher in infants of diabetic mothers (P=0.01). Conclusion: The prevalence of gestational diabetes is high in the region of Shahdad/ Kerman and history of stillbirth has the highest correlation with GDM. Therefore, screening of gestational diabetes and its risk factors in this community seems necessary. Keywords: Gestational diabetes, Prevalence, Risk factors, Pregnant women Citation: Nazari Robati F, Khanjani N, Tabasi Nezhad N, Rezabeigi Davarani E, Mohseni M. The Prevalence of Gestational Diabetes and Factors Affecting it in a Health Care Center. Journal of Health Based Research 2017; 2(4): 307-317.